WANPRESTASI TERHADAP PELAKSANAAN PEMBAYARAN KLAIM DALAM PERJANJIAN ASURANSI PENDIDIKAN - Dewi, Sri Amanda; Wardani, Susilo (The Juris, 2024)
This study aims to determine and analyze the implementation of the agreement between the insured in the Education insurance at PT. AJB Bumiputera Purwokerto and to determine and analyze the legal efforts to resolve the default on the payment of education insurance claims made by PT. AJB Bumiputera 1912 Purwokerto. The data analysis method in this study adopts the normative legal method descriptively to describe the current state of the subject or object of research based on the observed facts. The results of the first study showed that the implementation of the insurance agreement gave rise to rights and obligations agreed upon between the insured and the insurer, namely PT. AJB Bumiputera 1912 Purwokerto. These rights and obligations include the fulfillment of payment of education insurance claims in accordance with the provisions stated in the policy. After the agreement was implemented, the policy payment to the insured at the policy maturity date did not receive payment so that the insurer had committed a default in the form of delays in payment of education insurance claims for PT. AJB Bumiputera 1912 Purwokerto. The results of the second study were efforts to resolve disputes over defaults due to late payment of claims by PT. AJB Bumiputera 1912 Purwokerto the insured demands compensation through mediation, lawsuit, and arbitration.